Evaluasi Program Sanitasi Total Berbasis Masyarakat Pada Pilar Pertama Stop Buang Air Besar Sembarangan (BABS) Di Desa Kelong Kecamatan Bintan Pesisir Kabupaten Bintan Tahun 2022 - Siti Utari, Diah; Suherry, Suherry; Mukhlis, Suhardi; Marzalinda, Salneta; Sujono, Agus; Jenawi, Billy (STISIPOL Raja Haji, 2024)
Bintan Regency is one of the districts/cities in Indonesia that implements the STBM program in order to improve sustainable clean and healthy lifestyles by reducing the problem of open defecation in Bintan Regency. Kelong village is one of the villages that implements STBM, but Kelong village has not been declared an Open Defecation Free (ODF) village/sub-district because some of the people still build houses above the sea so they still practice defecation even in private. The aim of this research is to evaluate the First Pillar Community-Based Total Sanitation program to Stop Open Defecation (BABS) in Kelong Village, Bintan Pesisir District, Bintan Regency. The type of research used is evaluative analysis with a qualitative approach. The informants in this research were employees of the Bintan District Health Service, Kelong Community Health Center sanitarian workers in the field of environmental health, employees of the Public Works, Spatial Planning and Land Services and the Kelong village community who received benefits from the STBM program. The data collection tools used were observation, interviews and documentation. Next, a qualitative analysis was carried out. From the research results, it is known that the implementation of the STBM program in Kelong Village is still not optimal. Suggestions that can be given for this research are that the relevant agencies should respond more to reports or complaints from the public regarding the communal septic tank facilities that have been built in Kelong Village.